2017
DOI: 10.15171/jnp.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis as a common urinary system manifestation of inflammatory bowel diseases; a clinical review and meta-analysis

Abstract: Context: The extra-intestinal manifestations of inflammatory bowel disease (IBD) are common and involve other organs or systems for example; urinary system. Evidence Acquisitions: For this review, we used a variety of sources by searching through Web of Science, PubMed, EMBASE, Scopus and directory of open access journals (DOAJ). Results: Urinary complications may occur in up to 22% of patients and nephrolithiasis or renal/kidney stones have been suggested to be a common manifestation of disease in forms of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Inflammatory bowel disease patients had increased incidence of developing nephrolithiasis as well as urolithiasis . In light of this phenomenon, plenty of studies aimed to investigate the risk factors or decipher its possible mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease patients had increased incidence of developing nephrolithiasis as well as urolithiasis . In light of this phenomenon, plenty of studies aimed to investigate the risk factors or decipher its possible mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxaluria by definition is as an excessive oxalate urinary execretion. Clinical studies show that enteric hyperoxaluria (greater than 48 mg/24hr) is more prevalent in CD than in UC [3] [49]. Many findings have demonstrated that CD patients who have undergone surgical procedures such as ileocecal resection, intestine bypass and total colectomy, are at higher risk to develop secondary hyperoxaluria [47].…”
Section: Nephrolithiasismentioning
confidence: 99%
“…Human stones are known to have both kinds of organic and inorganic mineral components in which the inorganic part is 2-3% lower by weight and it acts like a template initially as rest is formed by proteins (64%), glycolipids, carbohydrates and GAGs [22]. It is highly secreted (with uniquely glycosylated fragments at c-terminal) into the urine in response to an infection and serves as an indicator of lithiasis [25].…”
Section: Vkorc1 (Vitamin K Epoxide Reductase Complex Subunit 1)mentioning
confidence: 99%